Genetic diversity and antigenic variation of trypanosoma evansi in Malaysia - Watanabe, Mahira (2012)
To investigate the genetic diversity of Trypanosoma evansi field isolates in Peninsular Malaysia, 42 isolates from cattle, deer and buffalo from eight farms were analysed using five microsatellite markers and a tandemly repeated coding sequence, MORF2-REP. A total of 30 alleles and eleven multilocus genotypes (MLGs) identified from across six loci revealed genetic polymorphism among the local isolates. The high fixation index (Fst) and Nei’s genetic distances were all indicative of genetic sub-structuring within the isolates. Nei’s genetic distances showed less allelic diversity between cattle and deer isolates and greater diversity between deer and buffalo isolates. The isolates from buffalo shared the same MLG and clustered together in the unweighted pair-group mean average (UPGMA) and neighbor-joining (NJ) trees, the deer isolates formed three sub-groups and the cattle isolates formed a number of different groups. Among the cattle isolates a number of MLGs were shared among isolates originating from different farms. Some MLGs were however unique to certain hosts or farms such as the MLGs observed in the deer isolates. The genotypes observed in the deer breeding centre were of significance as these pathogenic strains were responsible for an outbreak of trypanosomiasis which contributed to more than 27% of all deaths at the centre. The high number of repeated MLGs and high heterozygote excesses found in this study were supportive of a clonal population structure of this parasite. In order to investigate the antigenic repertoire of T. evansi isolates in Malaysia in the course of a natural infection, variant surface glycoproteins (VSGs) expressed in the field strains were isolated, cloned and characterized. Out of the 41 VSGs isolated from 32 T. evansi field isolates, nine were identified as novel VSGs which did not have close homologues in the databases. Ten of the VSGs were identical or highly similar to each other while 31 VSGs were distinct. Some of the identical VSGs were shared between isolates originating from different host species and farms suggesting that the antigenic repertoire had no constraints placed on it by the host species or geographical location. Most of the VSGs expressed by field isolates had typical N- and C-terminal domain structures. The N-terminal domains showed high sequence diversity as compared to the more conserved C-terminal domains. As there were no conserved motifs located in the N-terminal domain, the VSG coat remains a poor candidate for vaccine development and diagnostics. In an attempt to elucidate the complex process of antigenic variation, the antigenic repertoire of T. evansi was investigated in three goats experimentally infected with a local T. evansi field isolate. The VSGs expressed during the course of infection were isolated, cloned and characterized. Three major parasitaemic waves were observed in all three animals from which combinations of major and minor VSG populations were isolated. A total of 190 VSGs from the three animals were isolated during the course of infection which were divided into 48 distinct groups. The order of expression of major VSGs among the infected goats followed a loose hierarchy. Some VSGs expressed during the early stages of infection were expressed again during the later stages of infection. In conclusion, the data revealed high genetic diversity among the Peninsular Malaysia isolates of T. evansi which possessed a large antigenic repertoire. A loose hierarchy in the order of expression of major VSGs was observed in goats infected with a local field isolate of T. evansi.